Inequalities Between Reciprocals of Means - Elezović, Neven; Mihoković, Lenka (Sarajevo Journal of Mathematics, 2024)
The subject of this paper is linear combinations of reciprocal values of classical bivariate means and their behavior for translated values of the arguments. Based on the known asymptotic expansions some optimal parameters were obtained.